Emissões de gases de efeito estufa em resposta ao modo de aplicação de dejetos de suínos e ao uso de inibidor de nitrificação na sucessão trigo/milho em latossolo - Arenhardt, Marlon Hilgert (2016)
The greenhouse gases (GHG) emission in annual crops depends on soil conditions, climate and management of each site. Even the importance of no-till system in the grain production in the southern region of the country, the agricultural practices effect in the emission of the main greenhouse gases (CO2, N¬O and CH4) it is still little known, especially in Latossolos. Even more scarce are the works involving the use of pig slurry (PS) as fertilizer, the injection of PS or the use of nitrification inhibitors on GHG emissions under these conditions. Therefore, the aim of this study was to evaluate the GHG emissions in a Latossolo that is representative of Planalto of Rio Grande do Sul, in response to PS application method (injection x surface application) with or without the use of nitrification inhibitor Dicyandiamide (DCD). A field experiment was conducted in a Latossolo Vermelho aluminoférrico típico, near UFSM Campus in Frederico Westphalen, RS, from June 2014 to April 2015 with the wheat/corn no-till cropping system. The experimental was a randomized block design with four replicates with the following treatments: control (TEST), Mineral fertilizer (NPK), liquid pig slurry (PS) applied to surface (SUP), PS applied on surface with nitrification inhibitor DCD (SUP + IN), DLS injected into the soil (INJ) and PS injected with DCD (INJ + IN). GHG emissions were evaluated by static cameras, with GHG concentrations determined by gas chromatography . Most of the emissions of CO2 and N2O occurred in the summer during maize crop. The PS application increased N2O emission five times compared with TEST, regardless of PS application method. When DCD is used with manure N2O emissions were reduced by 50% with PS surface application and 32% when it was injected into the soil. The N2O emission factor ranged from 0,08 to 0.66% and it is lower than the average of 1 % of N applied established by IPCC. The CO2 emission was not affected by manure application during wheat crop season while increase until 69% in maize crop season. The higher emission was in SUP treatment and we realize that occurred additive effect of reapplication treatments. The soil is a CH4 sink independent treatment, with an average uptake of 277 g C-CH4 ha-1 in wheat crop and 266 g C-CH4 ha-1 in maize crop. The results of this study indicate that PS injection in Latossolo at a wheat/corn no-till cropping system does not increases the emission of CO2, N2O and CH4 in relation to surface application. Also, the addition of nitrification inhibitor DCD to PS helps to mitigate N2O emissions, regardless of the PS application method.